Análisis comparativo económico de un edificio aporticado de cinco (5) pisos diseñado con la nueva norma nsr-10 y nsr – 98 en nivel de disipación de energía especial en la ciudad de Santiago de Cali (2014)
The city of Santiago de Cali is a region that is located in an area of high seismic risk, which threatens the stability of its inhabitants in danger at any time. Faced with this reality of natural, non-leaking buildings, so in the course of the history of the city, have been studying and analyzing various forms and processes to improve the structures, so that no occasions in an earthquake much damage to the inhabitants of the buildings. The project poses which of the two standards NSR-98 or NSR-10 are improvements in implementation of both safety and cost to produce five-story building buildings, taking into account the risks of high-level earthquakes. The paper aims to model a five-floor building in high risk area, specifically in the city of Santiago de Cali Colombia applying standard NSR-10 Earthquake Resistant, compared to the standard NSR – 98. The importance of the project is in the security of the capital investment in the purchase of the property in a particular area of the country, especially in the city of Santiago de Cali, which facilitates analyzing whether the legislation actually makes up one of the problems of regulation to area high risks